2022
DOI: 10.7759/cureus.21551
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Substance Use and Mental Health Disorders: Prior Treatment/Admission as a Predictor of Criminal Arrest Among American Youths

Abstract: Background: There is a dearth of literature with regards to substance use disorder (SUD) treatment outcomes and criminal arrest relationships.Aim: We aimed to examine the association between criminal arrest within a month prior to SUD treatment admissions among 12-to 24-year-old Americans and the role of recurrent or prior SUD treatment.Methods: The 2017 United States Substance Abuse and Mental Health Services Administration (SAMHSA) Treatment Episode Data Set -Admissions (TEDS-A; N = 333,322) was used for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Of most concern, a history of arrest was strongly related to significantly higher rates of substance use among both gender groups and was more strongly pronounced among women. Previous research found that substance use disorder (SUD) substantially increased the risk of involvement in the criminal justice system; moreover, concurrent mental illness and SUD elevated the odds of arrest (Magee et al, 2021 ; Nkemjika et al, 2022 ; Prince & Wald, 2018 ). This study adds to the literature by providing findings for the young population, separately for men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Of most concern, a history of arrest was strongly related to significantly higher rates of substance use among both gender groups and was more strongly pronounced among women. Previous research found that substance use disorder (SUD) substantially increased the risk of involvement in the criminal justice system; moreover, concurrent mental illness and SUD elevated the odds of arrest (Magee et al, 2021 ; Nkemjika et al, 2022 ; Prince & Wald, 2018 ). This study adds to the literature by providing findings for the young population, separately for men and women.…”
Section: Discussionmentioning
confidence: 99%